Fabella Syndrome of Bilateral Knee with Common Peroneal Nerve Compression Neuropathy - Shiraaj Zainul Abiddin; Mohd Hisham Mohd Isa (USIM Press, 2024)
Vol. 8 (2022): Special Issue on Communicable and Non-Communicable Disease, Multidisciplinary Case Reports